Time Series Analysis and Forecasting with GPT-4o. - Zhang, Alina (linkedin.com, 2024)
Master time series analysis and forecasting with GPT-4o. Apply fundamentals and advanced techniques with the pumpkin carriage framework and get started predicting future trends.